2010
DOI: 10.1111/j.1526-4637.2010.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Ganglion Impar Block: A Technical Report

Abstract: In cases where the cleft cannot be readily seen on AP and lateral fluoroscopy, we have found ultrasound to be of assistance. Ultrasound does not replace fluoroscopy, because lateral fluoroscopy is still required to establish safe depth, and correct site of injection. However, ultrasound can be helpful when fluoroscopy alone is insufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 8 publications
(7 reference statements)
1
21
0
1
Order By: Relevance
“…These results were confirmed in a volunteer study where a nerve stimulator was used [3]. In a series of 20 patients with meralgia paresthetica, all had resolution of their symptoms within 2 weeks of injection; however, four patients required repeat injections at 1 week [73] • • Other US-guidance has also been described for injections of the ganglion of impar [75], pudendal nerves [76] and abdominal cutaneous nerves [77]. These studies demonstrated feasibility of the methods rather than superiority of the technique.…”
Section: • Lateral Femoral Cutaneous Nervesupporting
confidence: 61%
“…These results were confirmed in a volunteer study where a nerve stimulator was used [3]. In a series of 20 patients with meralgia paresthetica, all had resolution of their symptoms within 2 weeks of injection; however, four patients required repeat injections at 1 week [73] • • Other US-guidance has also been described for injections of the ganglion of impar [75], pudendal nerves [76] and abdominal cutaneous nerves [77]. These studies demonstrated feasibility of the methods rather than superiority of the technique.…”
Section: • Lateral Femoral Cutaneous Nervesupporting
confidence: 61%
“…Following a PubMed literature search defining "ultrasound", "ultrasonography" and "ganglion impar" we found only one reference related to a blockade of the ganglion impar using ultrasound imaging as part of the technique. The article describes the use of ultrasound to identify the sacrococcygeal junction as the initial stage in performing the technique with lateral fluoroscopy utilised to gauge needle depth (Lin et al, 2010). Another article describes a retrospective case series of various sympathetic blocks performed under ultrasound, including ganglion impar block (Bhatnagar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…By blocking the sympathetics, we can overcome the problem mentioned above. Even though ultrasound [16] can help in administration of the block, we gave it by the classical approach only.…”
Section: Discussionmentioning
confidence: 99%